2010
DOI: 10.1097/iae.0b013e3181d2f172
|View full text |Cite
|
Sign up to set email alerts
|

Combined Ranibizumab and Photodynamic Therapy to Treat Exudative Age-Related Macular Degeneration

Abstract: Combined customized PDT + ranibizumab treatment can achieve visual results similar to those obtained with intravitreal monotherapy with the advantage of fewer intravitreous injections and reduced potential for adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Only 4 eyes (10.5%) in this study showed a recurrence of exudative changes. Mataix et al reported that 39.6% of patients were successfully treated with only a single initial dose (PDT and ranibizumab) and remained stable for 12 months [10]. Thus, combined treatment of PDT and IVR might be sufficient to scar the CNV lesion in about half of exudative AMD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 4 eyes (10.5%) in this study showed a recurrence of exudative changes. Mataix et al reported that 39.6% of patients were successfully treated with only a single initial dose (PDT and ranibizumab) and remained stable for 12 months [10]. Thus, combined treatment of PDT and IVR might be sufficient to scar the CNV lesion in about half of exudative AMD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ranibizumab monotherapy for exudative AMD required 5.2 ± 2.8 IVR during a followup of 12 ± 4.3 months when ranibizumab monotherapy was performed on an as-needed basis [13]. Mataix et al showed results of combined therapy of PDT and ranibizumab: in that study, 92.3% patients showed improved vision or at least avoided moderate loss of vision over 1 year with 1.22 PDT sessions and 2.37 IVR [10]. Their results were similar to our results even though they performed IVR within 48 to 60 hours after PDT.…”
Section: Discussionmentioning
confidence: 99%
“…The Verteporfin In Photodynamic Therapy Study (VIP) trial demonstrated that patients with AMD lost less lines of vision when treated with PDT [15], however Axer-Siegel et al [16] found those patients with serous PED may not benefit at all from PDT. More recent studies have reported success in decreasing the number of required anti-VEGF injections and stabilizing vision with a combination of antiVEGF and PDT including for patients with PED [17,18]. There are currently clinical trials in the pipeline investigating some theories that could result in management of this subset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other studies report stabilizing the lesion with one single dose of PDT induction + anti-VEGF after twelve months follow-up. The percentage of cases varies in different studies ranging from 39.6% to 46% to 48% (Mataix, 2010;Smith, 2008).…”
Section: Other Studiesmentioning
confidence: 99%